1984
DOI: 10.4141/cjps84-137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Row Spacing and Seeding Rate on Rapeseed Yield in Northwest Alberta

Abstract: The effect of row spacing and seeding rate on the yield of Brassica campestris L. and B. napus L. was studied for 2 yr in northwest Alberta. Rows were spaced 7.5, 15 and 23 cm apart with seeding rates of 7 and 14 kg/ha at each spacing. Decreasing row spacing from 23 cm to 15 cm and from 15 cm to 7.5 cm increased yields by an average llVo and 337o, respectively. Seeding rate had no significant effect on yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 3 publications
5
33
2
Order By: Relevance
“…However, investigations by other workers, conducted under conditions free from economic infestations of pests, determined that greatest yields of canola occurred at narrower, rather than wider, row spacings. Kondra (1975) found that greater yields occurred in 15-cm rows compared with 23-, 31-or 61-cm rows, and Christensen and Drabble (1984) determined that row spacings of 7.5 cm resulted in 36% higher yields than spacings of 15 cm. Morrison et al (1990) found that plants seeded in 15-cm rows had greater yields than those in 30-cm rows, and lodged to a lesser degree.…”
Section: Discussionmentioning
confidence: 99%
“…However, investigations by other workers, conducted under conditions free from economic infestations of pests, determined that greatest yields of canola occurred at narrower, rather than wider, row spacings. Kondra (1975) found that greater yields occurred in 15-cm rows compared with 23-, 31-or 61-cm rows, and Christensen and Drabble (1984) determined that row spacings of 7.5 cm resulted in 36% higher yields than spacings of 15 cm. Morrison et al (1990) found that plants seeded in 15-cm rows had greater yields than those in 30-cm rows, and lodged to a lesser degree.…”
Section: Discussionmentioning
confidence: 99%
“…6 and l2 kg ha-r (Kondra lg75: lg7li Degenhardt and Kondra l98lb). Christensen and Drabble (1984) found no significant yield differences between seedins rates of 7 and l4 kg ha I in northwestJrn Alberta. In Saskatchewan, Clarke and Simpson (1918) and (Goeze) and Psylliodes punctulatas (Melsheimer)).…”
mentioning
confidence: 89%
“…(Kondra 1975, l9l7). Clarke and Simpson (1978) and Clarke et al (1978) suggested that higher yields could be achieved with increased rates of seeding, whereas studies conducted by Christensen and Drabble (1984) and Degenhardt and Kondra (1981) indicated seeding rates had no significant effect on yields. Crop heights were reduced with the two greatest seeding depths compared with the two shallowest depths (Table 2).…”
mentioning
confidence: 92%
“…Plant density at 10 days after emergence and at maturity ofyellow mustard sown at five dates over a 5-year period (1984 and 1986-1989) Table 7. Days to emerge and mature for yellow mustard sown at five dates over 5 years (1984 and 1986-1989) at Clarke and Simpson (1978) and by Christensen and Drabble (1984) Hegarty (1977Hegarty ( , 1978 For personal use only.…”
Section: Rate Of Seedingmentioning
confidence: 99%